Exploring the effects of local community Involvement in the implementation of Government funded projects - Mumuni, Abubakari Amuquandoh (2021)
A thesis submitted to the Department of Construction Technology and Management, College of Art and Built Environment, in partial fulfillment of the requirement for Degree of Master of Science.